Plasma Methionine Sulfoxide in Persons with Familial Alzheimer’s Disease Mutations - Ringman, John M.; Fithian, Andrew T.; Gylys, Karen; Cummings, Jeffrey L.; Coppola, Giovanni; Elashoff, David; Pratico, Domenico; Moskovitz, Jackob; Bitan, Gal (Dementia and geriatric cognitive disorders, 2012)
Background: Convergent evidence suggests that oxidative stress plays a central role in the pathology of Alzheimer’s disease (AD). We asked if consequently, oxidation of methionine residues to methionine sulfoxide (MetO) was increased in plasma proteins of persons carrying familial AD (FAD) mutations. Methods: Plasma was collected from 31 persons from families harboring PSEN1 or APP mutations. Using Western blot analysis with a novel anti-MetO polyclonal antibody, MetO levels were measured and compared between FAD mutation carriers (MCs) and non-mutation carrying (NCs) kin. Results: A MetO-positive 120-kDa gel band distinguished FAD MCs and NCs (mean 11.4 ± 2.8 vs. 4.0 ± 3.1, p = 0.02). In a subset of subjects for whom both measurements were available, MetO levels correlated well with plasma F2-isoprostane (r = 0.81, p < 0.001) and superoxide dismutase 1 (r = 0.52, p = 0.004) levels. Conclusion: Our data provide evidence for elevated MetO levels in persons carrying FAD mutations that correlate with other indices of oxidative stress and suggest that plasma oxidative stress markers may be useful for diagnosis of AD.